The Influence of Digital Marketing and Service Quality on Consumer Purchase Decisions at PT. Roti Ketawa Siantar Waka-Waka - Jopinus Saragih; Mhd. Ramadhan; Nurmasdalifah Nurmasdalifah; Jumadiah Wardati (International Journal of Economics, Commerce, and Management, 2026)
Digital marketing and service quality have become important determinants of consumer purchasing behavior in the increasingly competitive food and beverage industry. This study aims to examine the partial and simultaneous effects of digital marketing and service quality on consumer purchase decisions at PT. Roti Ketawa Siantar Waka-Waka, Pematangsiantar, Indonesia. A quantitative research approach was employed using a survey method involving 100 consumers selected through purposive sampling. Data were collected using structured questionnaires and analyzed with SPSS version 25. The analysis included validity and reliability testing, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The findings indicate that digital marketing has a positive and significant effect on purchase decisions (t = 2.231; p = 0.028), while service quality also has a positive and significant effect (t = 7.963; p < 0.001). Simultaneously, digital marketing and service quality significantly influence consumer purchase decisions (F = 120.872; p < 0.001), explaining 71.4% of the variance in purchasing decisions (R² = 0.714). These findings suggest that improving digital marketing strategies alongside maintaining high service quality can effectively enhance consumer purchase decisions. The study contributes to the understanding of consumer behavior in the food industry and provides practical recommendations for business managers seeking to strengthen customer engagement and competitiveness.